Finite Element Modelling of Unpaved Road Reinforced with Geosynthetics. (2017) - Calvarano, Lidia Sarah; Leonardi, Giovanni; Palamara, Rocco
Abstract: The technique of soil mechanical stabilization, using geosynthetics, is extensively used in the construction of unpaved roads with a low volume of traffic. Unpaved roads consist of unbound granular bases overlying cohesive subgrades. When built on weak subgrades, these roads are subject to problems like excessive rutting and mud-pumping, increasing maintenance costs and usually leading to periodic interruptions to traffic. Particularly, the field applications of geosynthetic reinforcement placed above a weak subgrade can markedly improve the performance of these roads decreasing permanent vertical deformations, increasing lateral restraint ability, which results in increased pavement service life or reduced base thickness to carry the same number of load repetitions. This paper focuses on providing a numerical investigation using a bi-dimensional Finite Element Method (FEM), using ABAQUS software, to analyze the improvement of reinforced unpaved road under repeated wheel traffic load conditions in terms of aggregate base course thickness saving.